2020
DOI: 10.1111/jdi.13467
|View full text |Cite
|
Sign up to set email alerts
|

Plasma xanthine oxidoreductase activity in Japanese patients with type 2 diabetes across hospitalized treatment

Abstract: Aims/Introduction Xanthine oxidoreductase (XOR) is an enzyme that catalyzes hypoxanthine and xanthine to xanthine and uric acid, respectively. Plasma XOR activity has recently been measured in humans. However, limited information is known about plasma XOR activity in patients with type 2 diabetes mellitus, and its changes after short‐term glycemic control treatment. Materials and Methods We enrolled 28 Japanese patients (10 men/18 women) with type 2 diabetes mellitus who were hospitalized to undergo medical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…It has been reported that XOR activity was positively correlated with HbA1c in patients with diabetes. Shortterm carbohydrate-restricted treatment (2 weeks of inpatient treatment) reduced plasma XOR activity, suggesting that diabetes may play an important role in regulating XOR activity [32]. Indeed, the present study showed that the HbA1c levels were highest in patients with the highest XOR quartile, which is in line with the report's findings mentioned above (Table 2) [32].…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that XOR activity was positively correlated with HbA1c in patients with diabetes. Shortterm carbohydrate-restricted treatment (2 weeks of inpatient treatment) reduced plasma XOR activity, suggesting that diabetes may play an important role in regulating XOR activity [32]. Indeed, the present study showed that the HbA1c levels were highest in patients with the highest XOR quartile, which is in line with the report's findings mentioned above (Table 2) [32].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, elevated plasma XOR activity has been reported to be associated with increased CVD events in heart failure patients with preserved ejection function [42] and higher mortality in cardiovascular intensive care patients [43], as well as an independent predictor of CVD events in CKD and hemodialysis patients [10]. Interestingly, Kawachi et al [44] demonstrated that short-term glycemic control treatment (2 weeks hospitalization) decreased plasma XOR activity in patients with type 2 DM. Together, findings showing an association between glycemic control and plasma XOR activity in patients with type 1 diabetes [36], patients under hemodialysis in our previous study [18], and pre-dialysis CKD patients in the present study suggest the importance of glycemic control in regard to decreased XOR, possibly leading to a decrease in CVD events.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Recently, relationships between various clinical features and the level of plasma XOR activity measured by the procedure used in our present study have been reported. For example, plasma XOR activity is related to obesity and habitual smoking in the general population [35], vascular endothelial dysfunction assessed by flow-mediated dilation in patients with type 1 diabetes [36], liver dysfunction in T2DM patients [37], the prevalence rate of coronary artery spasm [38], and adverse clinical outcomes in patients with heart failure but with a preserved ejection fraction [39], as well as the requirement for cardiovascular intensive care [40]. Previous studies demonstrated that XOR activity is upregulated in patients with diabetic vascular complications [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%